Patient Choice of Health Care Providers in China: Primary Care Facilities versus Hospitals. Issue 1 (1st December 2020) - Zhang, Anwen; Nikoloski, Zlatko; Albala, Sarah Averi; Yip, Winnie; Xu, Jin; Mossialos, Elias
ABSTRACT: As China's health system is faced with challenges of overcrowded hospitals, there is a great need to better understand the recent patterns and determinants of people's choice between primary care facilities and hospitals for outpatient care. Based on recent individual-level data from the China Health and Retirement Longitudinal Survey (CHARLS) and official province-level data from China health statistical yearbooks, we examine the patterns of outpatient visits to primary care facilities versus hospitals among middle-aged and older individuals and explore both supply- and demand-side correlates that explain these patterns. We find that 53% of outpatient visits were paid to primary care facilities as opposed to hospitals in 2015, compared to 60% in 2011. Both supply and demand factors were associated with this decline. On the supply side, we find that the density of primary care facilities did not account for this decline, but higher densities of hospitals and licensed doctors were associated with lower use of primary care facilities. On the demand side, we find that individuals with higher socioeconomic status and greater health care needs were less likely to use primary health care facilities. Our findings suggest that a high concentration of health care professionals in hospitals diverts patients away from primary care facilities. Staffing the primary care facilities with a well-trained health care workforce is the key to a well-functioning primary care system. The findings also suggest a need to address demand-side inequality issues.